Standardizing Editorial Process Towards Quality - Thapa, Deeptara Pathak; Pradhan, Sushmita (Nepal Journal of Dermatology, Venereology & Leprology, 2022)
A quality journal depends upon well-organized, structured, and efficient editorial activity. In addition, it is also determined by robust peer-review, pellucid focus and scope of the journal, amiability to authors, and open access for scholarly exchange of scientific research for paramount researchers worldwide.